The status of professional autonomy and its predictors in clinical nurses in Iran - Leila Rouhi Balasi; Maryam Hazrati; Asieh Ashouri; Abbas Ebadi; Nasrin Elahi (Wiley, 2024)
Abstract Aim The present study aimed to assess professional autonomy among clinical nurses and identify its predictors using a native and contemporary tool, which is in line with the recent advancement in nursing professionalism in Iran. Design The study used an analytical cross‐sectional design. Methods A total of 1601 nurses working in medical centres nationwide under the Ministry of Health participated in the study. The research instrument consisted of two parts, including individual and organizational characteristics and a questionnaire on clinical nurses' professional autonomy. Data analysis involved descriptive and inferential statistics as well as multiple logistic regression analysis using SPSS software. Results The results indicated that the total professional autonomy score among clinical nurses was 75.86 ± 12.03, with the majority (n = 1262, 78.9%) reporting high professional autonomy. Multiple logistic regression analysis revealed that nurses with 5-15 years of experience had 1.82 times higher odds (95% confidence interval: 2.47-1.35) of having high professional autonomy compared to those with less than 5 years of experience. Similarly, nurses with over 15 years of experience had 2.25 times higher odds (95% confidence interval: 1.56-3.26). Head nurses had 4.56 times higher odds (95% confidence interval: 2.60-7.99) of having high professional autonomy compared to clinical nurses. Conclusion Educational interventions to enhance the professional autonomy of less experienced nurses, with more experienced nurses serving as role models, are recommended. Additionally, measures such as supporting nurses, providing effective communication training and empowering nurses are essential to promote professional mutual respect among nurses. No Patient or Public Contribution This study explored professional autonomy in clinical nurses in Iran. No patient or public contribution was investigated.